A formação em contexto de professoras dos bebês e das crianças bem pequenas: análise de um processo formativo na creche - Chaves, Edlane de Freitas (2020)
The formation continues of the teachers who work with babies and very small children are the theme of investigation from this search at the context of daycare center. The general objective was to analyze the perspective of the teachers who work with babies and very small children about the possibility of the one process of formation in the context contributed to the transformation of the pedagogical practices that perform in the daycare center. Like this, the goals of specific identified in to participate with the teachers what are your main needs of formatives in relationship to the job that they accomplish in the daycare center. Learn the perspectives of the teachers about the process of formation in the context, developed with these professionals; comprehend the perspective of the teachers about the possible contributions of the formation process in the context to the transformation of the pedagogical practices developed by these subjects in a day-to-day basis day in the daycare center. The expanse in the professor's formation was the reflections of authors as important as Nóvoa (1999), Formosinho (2009) and Imbernon (2010, 2016), such as in addressing issues related to the early theme of children education. Rocha's contributions (1999), Faria (1999), Cruz (1996, 2010), Campos (1994, 2006), Kramer (2008), Oliveira-Formosinho (2000, 2011, 2016) and Barbosa (2016), among others authors. The research was carried out in a public daycare center in municipality principles of a qualitative approach. The contextual formation (assessment/ diagnosis of the situation, planning development, and assessment formation together with the teachers was motivated by the objective of the search for action type of collaborative. The observation participant and the interview half structure (individual and collective) were fundamental to the construction of the data processing and the inquiry of the proposal pedagogical of the institution was a strategy complementary to reach the goals of the investigation. The analysis of the data constructed from the observation using the Environment assessment scale for infants and young children (ITERS - R Scale) made it possible to identify the main training needs to be solved in the daycare center, with the organization of the environment being the trigger theme to be discussed in the contextual training. The analysis of the interviews provided access to the teachers' perceptions about the contributions of the training process in the context in which they participated in the daycare center. In general, they understand this, the formation was a process with share and constructions collective valued your character or participative highlighted in the strong relationship referred with the context of the daycare center, with focus on the formatives needs of their teachers, if it constituted the opportunity for the expansion of relevant knowledge to reflect on their teacher's actions, and therefore, for improvement of those involved in the process. They emphasized that the state on the Participatory Pedagogies caused important reflections and contribute to changes in conceptions (of children, of early childhood education, the role of the daycare teacher), which had repercussions on some transformations: in the management of postures as teachers, in the relationship with children, the face of the changes initiated in the context, some challenges remain to enable a pedagogical practice that respects the of rights of the children in the attitudes of some teachers, who have not yet opened themselves in the proposed changes, the positioning of the board, which did not assume the formative character of its pedagogical function in the daycare center and acquisition of equipment and materials (such as children's literature books; toys, in equipment suitable for accommodating babies at times of feeding), aspects that indicate the need for further formation in the context daycare center investigate.